On rebellion - Knox, John (Cambridge texts in the history of political thought, 1994)
John Knox's First Blast of the Trumpet against the Monstrous Regiment of Women, one of the most notorious political tracts of the sixteenth century, has been more often referred to than read. Its true significance as one of a series of pamphlets which Knox wrote in 1558 on the theme of rebellion is therefore easily overlooked. This new edition of his writings includes not only The First Blast, but the three other tracts of 1558 -The Letter to the Regent of Scotland, The Appellation to the Scottish Nobility, and The Letter to the Commonalty of Scotland - in which Knox confronted the problem of resistance to tyranny. Related material, mostly drawn from Knox's own History of the Reformation in Scotland, illuminates the development of his views before 1558 and illustrates their application in the specific circumstances of the Scottish Reformation and the rule of Mary Queen of Scots. This edition thus brings together for the first time all of Knox's most important writings on rebellion.